2017
DOI: 10.1155/2017/7536364
|View full text |Cite
|
Sign up to set email alerts
|

Optical and Structural Properties of Solvent Free Synthesized Starch/Chitosan-ZnO Nanocomposites

Abstract: The objective of this work is to develop an environmentally friendly method for preparation of ZnO nanocomposites. ZnO nanocomposites were prepared by three natural fibers such as coir, sawdust, and chitosan using aqueous solution of zinc chloride and sodium hydroxide. The functional groups of ZnO, C=O for polysaccharide, and N-H bending vibration of amine were confirmed by FTIR spectroscopy. A new high intensity absorption band has been observed at 424 cm −1 which corresponds to the E 2 mode of hexagonal ZnO.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…In addition, the CS peak vanished due to the higher crystalline properties of ZnO. Furthermore, we estimated the crystallite size of the nanocomposites using Debye-Scherer’s formula to help deduce their microstructural characteristics [ 56 , 57 ]. Consequently, the crystallite sizes for the CS–ZnO and CS–ZnO–GO hybrids were estimated as 23.2 and 19.5 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the CS peak vanished due to the higher crystalline properties of ZnO. Furthermore, we estimated the crystallite size of the nanocomposites using Debye-Scherer’s formula to help deduce their microstructural characteristics [ 56 , 57 ]. Consequently, the crystallite sizes for the CS–ZnO and CS–ZnO–GO hybrids were estimated as 23.2 and 19.5 nm, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Chitosan is an important natural polymer for various applications including biomedical sensors, implants, and anti-microbial and microfluidic devices [ 12 , 18 , 19 , 20 ]. Nanocomposite materials based on chitosan with metal oxide materials have become attractive in recent years due to their synergistic behavior [ 21 ]. Recently, Sanmugam et al [ 21 ] successfully demonstrated the solvent free synthesis of chitosan-zinc oxide (ZnO) nanocomposites using chitosan and ZnCl 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Visible emission is widely observed on ZnO nanostructures and has been assigned to the recombinations of photoexcited electrons-holes being trapped at defect states including oxygen vacancies (V O ), zinc interstitials (I Zn ), zinc vacancies (V Zn ), and their complexes [2,6,14,16,17,20,[29][30][31]. Here, we put forward a plausible mechanism shown in Figure 5 to explain PL properties of the ZnO-PMMA composite.…”
Section: Resultsmentioning
confidence: 89%
“…Incorporation of ZnO into polymer matrix is a convenient way to stabilize the PL properties of ZnO and to add new functionalities to the polymer [6,13,19]. Herein, we observed unexpectedly that poly(methyl methacrylate) (PMMA) matrix quenches the original green-orange emission but enhances red emission of ZnO NPs.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation